Strategic framework for Commercial Real Estate Investment in CEE region. The Case of Commercial Real Estate in Prague, Czech Republic. - Burman, Ksenia; Tyll, Ladislav; Krause, Josef, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The goal of this thesis is to show on the real case study how to open successful shopping centre in Prague. For this I have analysed the industry, identified key success factors and future trends, prepared the CEE market outlook and compared the situation in CEE capitals. Then I moved to the case study for opening SC Bubny in Prague 7. I have made PESTLE analysis, described the project and its current situation, analysed the catchment area, competitors and created a customer profile according to demographic situation in the catchment area. Based on the research and trends I have made a concept for SC Bubny, including the size of the SC, leasing plan, events and services that should be offered and then assessed its profitability and prepared valuation. As a result I have received potentially successful shopping centre with good profitability ratios and a framework for opening a SC in Prague.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses